감마과정 기반 양방향 접합 트랜지스터 잔여수명 예측 - 이선재; 장중순; 유찬세; 김종호; 박상철 (신뢰성 응용연구, 2021)
Purpose: The gamma process was used to predict the remaining useful life of a bipolar junction transistor, which is a widely used electronic component. Methods: The proposed method consists of six major steps: 1) data collection via accelerated degradation test, 2) data conversion for the gamma process, 3) parameter estimation of the gamma process, 4) shape function estimation using a fitting procedure, 5) degradation model generation using the inverse power law and Arrhenius relation, and 6) prediction of the remaining useful life by estimating the failure criterion. Results: The degradation characteristic of a bipolar junction transistor is the beta (β) value (current gain), and the transistor is considered a failure when the β value deteriorates by 33.3%. Conclusion: This paper proposes a new method for predicting the remaining life of a bipolar junction transistor.
Keywords: Gamma Process; Accelerated Degradation Test; Remaining Useful Life; Bipolar Junction Transistor